KINERJA GURU SEBAGAI ASPEK STRATEGIS DALAM PENGELOLAAN SUMBER DAYA MANUSIA PENDIDIKAN - Kusumaningrum, Hesti; Chaerany, Chesia; Kholisah, Tri Ariqoh; Cahyani, Regita (Journal Education and Government Wiyata, 2024)
The article journal discusses importance of improving teacher performance as a strategic aspect in managing educational human resources. Evaluation of teacher performance, improvement through training and stimulant programs, and teacher work productivity are the main focus in creating an effective, efficient and quality educational environment.  Collaboration between teachers, school principals and education stakeholders is also needed to achieve this goal.  Evaluating teacher performance is essential to determine their competency in teaching and support their professional development.  Teacher productivity is a key factor in creating an effective educational environment, with a focus on individual and organizational dimensions. Increasing teacher performance can be achieved through developing competence, motivation, support and effective work environment management.  With in-depth attention to various strategic aspects regarding teacher performance, it is hoped that education in Indonesia can continue to develop in a better direction.  The method used in this research is a literature review by compiling a comprehensive article on the topic and taking several references from books and journals related to the material to be discussed.  Abstracts and keywords are also included in this journal, providing a comprehensive overview of the importance of improving teacher performance in creating effective and quality learning.